Influence of mixed modifier fluoride on tuning the AC and dielectric properties of xBaF2(50x)CaF250B2O3 glass system - Muhammad Noorazlan Abd Azis (Tanjung Malim, 2023)
Influence of mixed modifier fluoride on tuning the AC and dielectric properties of xBaF2(50x)CaF250B2O3 glass system by Muhammad Noorazlan Abd Azis